City of the dead - Kellerman, Jonathan (An Alex Delaware novel, 2022)
"Alex Delaware and Detective Milo Sturgis must uncover the connection between a brutally murdered psychologist and a victim they're unable to identify in this electrifying thriller from the #1 New York Times bestselling master of suspense. Two burly movers are heading back into Los Angeles from the dusty wasteland of Ojai when they hit a man-a naked man who appears out of nowhere. Master detective Milo Sturgis is called to the scene and senses immediately that something is amiss. As the Tesla-driving denizens of this well-off neighborhood begin to congregate, shielding their children's eyes or craning to get a better view, Milo realizes there's no way to identify this body. There's no ID. The victim could be anybody. And that's when Milo calls upon psychologist Alex Delaware. Milo and Alex get their first lead from a crotchety old man who lives down the block. If the victim was naked, he could have come from her house-a woman who has men coming in and out at all hours of the day and night. But what the duo sees from outside her barred windows will make things take another complicated turn: It's a scene of incredible horror. She is lying on the kitchen floor; there is blood everywhere. And when they get a closer look, Alex realizes he knows this woman. She's a fellow psychologist. When traces of DNA found underneath her fingernails point to a man who is not the first victim, the detection really begins. . . "--